Community oriented primary care in Tshwane District, South Africa: Assessing the first phase of implementation - Hans-Friedemann Kinkel; Tessa Marcus; Shehla Memon; Nomonde Bam; Jannie Hugo (AOSIS, 2013)
Background: Re-engineering primary health care is a cornerstone of the health sector reforminitiated nationally in South Africa in 2009. Using the concept of ward based NGO-run healthposts, Tshwane District, Gauteng, began implementing community oriented primary care (COPC) through ward based outreach teams (WBOT) in seven wards during 2011. Objectives: This study sought to gain insight into how primary health care providers understood and perceived the first phase of implementing COPC in the Tshwane district. Method: Qualitative research was performed through focus group interviews with staff of the seven health posts during September 2011 and October 2011. It explored primary health careproviders' understanding, perception and experience of COPC. Results: Participants raised organisational, workplace and community relationship issues in the discussions. Organisationally, these related to the process of initiating and setting up COPC and the relationship between governmental and nongovernmental organisations. Issues that arose around the workplace related to the job situation and employment status and remuneration of health post staff. Community related issues centred on the role and relationship between service providers and their communities. Conclusion: COPC touched a responsive nerve in the health care system, both nationallyand locally. It was seen as an effective way to respond to South Africa's crisis of health care. Initiating the reform was inevitably a complex process. In this initial phase of implementing COPC the political commitment of governmental and nongovernmental organisations was evident. What still had to be worked through was how the collaboration would materialise in practice on the ground.